2017
DOI: 10.1016/j.pmedr.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Perceived support from a caregiver's social ties predicts subsequent care-recipient health

Abstract: Most social support research has examined support from an individual patient perspective and does not model the broader social context of support felt by caregivers. Understanding how social support networks may complement healthcare services is critical, considering the aging population, as social support networks may be a valuable resource to offset some of the demands placed on the healthcare system. We sought to identify how caregivers' perceived organizational and interpersonal support from their social s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 15 publications
0
18
0
5
Order By: Relevance
“…To make it possible for older adults to live in the community, it is necessary to alleviate the burden on caregivers. Previous studies showed that community involvement had potential positive effects for both patients and family caregivers in long-term care (Barber 2013;Kelley et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To make it possible for older adults to live in the community, it is necessary to alleviate the burden on caregivers. Previous studies showed that community involvement had potential positive effects for both patients and family caregivers in long-term care (Barber 2013;Kelley et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when caregivers engage in social activities, this may also influence the health of care-recipients. In a study in the United States, Kelley, Lewis, and Southwell (2017) found that social engagement (religious services, went to a support group, visited with friends or family not living in the same home, participated in club meetings or group activities, or went out for enjoyment) for caregivers had a direct positive association with the care-recipient’s health.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the potential impact of social networks in health goes beyond the networks of patients. For instance, there is evidence that a caregiver's social engagement is associated with care-recipient's health [35]. Thus, interventions that target the social support needs of Latina breast cancer survivors and their caregivers may potentially affect breast cancer related outcomes.…”
Section: Discussionmentioning
confidence: 99%